2014
DOI: 10.1111/josi.12069
|View full text |Cite
|
Sign up to set email alerts
|

Discourse, Defiance, and Rationality: “Knowledge Work” in the “Obedience” Experiments

Abstract: In this article, I present a secondary qualitative analysis of archived audio data from two conditions (“voice‐feedback” and “women as subjects”) in Milgram's experiments. Using a perspective informed by rhetorical and discursive psychologies, I focus on the rhetorical strategies employed by participants. This highlights the use of strategies based around direct invocations of “knowledge.” Analysis explores the ways in which participants could use such strategies to challenge the experimenter's definition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
0
46
0
1
Order By: Relevance
“…In notes for a presentation to the American Psychology Association in the 1970s, he candidly observed that “the apparent objective nature of the film material conceals a subjective piece of film construction.” Indeed, he even considered reediting one of his own films (SMP Box 37, Folder 381). Stripped of their framing argument, the Obedience rushes provide valuable records worthy of further scrutiny as researchers continue to recover some of the lost narratives of Milgram's work (e.g., see Gibson, ; Haslam & Reicher, ; Russell, ).…”
Section: Resultsmentioning
confidence: 99%
“…In notes for a presentation to the American Psychology Association in the 1970s, he candidly observed that “the apparent objective nature of the film material conceals a subjective piece of film construction.” Indeed, he even considered reediting one of his own films (SMP Box 37, Folder 381). Stripped of their framing argument, the Obedience rushes provide valuable records worthy of further scrutiny as researchers continue to recover some of the lost narratives of Milgram's work (e.g., see Gibson, ; Haslam & Reicher, ; Russell, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult for people to resist a direct request or demand. It is likely, especially given the protests many participants made along the way (Gibson, ; Milgram, ), that even if at the beginning they adopted the task and role as their own, many of them were ready to abandon both. But even though they attempted to resist in response to the loud distress of the learner, many continued to comply for various length of time with demands and orders, such as “It is absolutely essential that you continue (Prod 3).” In the end, those who still were complying, resisted a final demand, usually made when the learner again loudly protested (Prod 4) “You have no other choice, you must go on,” probably both because it was made at a time when they were very intent to disengage, and its style or manner was rather absurd and resistance‐generating.…”
Section: Understanding Influences and Psychological Processes In The mentioning
confidence: 99%
“…First, even though Milgram () often emphasizes the ease of falling in the “trap of obedience” and the difficulty of disobedience, to an outside observer, the behavior of those who were willing to administer the maximum level of shock was not that different from that of those who refused to continue. As recently unearthed tapes show, both sets of participants signaled their concern, pleaded with the experimenter to stop the study, and made their objections heard (Gibson, ; Millard, ). It thus appears that for participants obedience was just as difficult as disobedience.…”
Section: Milgram's Theory: a Missed Opportunitymentioning
confidence: 99%